2022
DOI: 10.1002/ep.13875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermoeconomic optimization and exergoenvironmental analysis of an ejector refrigeration cycle integrated with a cogeneration system utilizing waste exhaust heat recovery

Abstract: Two cogeneration cycles based on gas turbines have been compared by means of thermoeconomic and environmental analyses. The analyzed cogeneration systems are gas turbine, organic Rankine cycle (GT + ORC) and an integrated system including gas turbine, organic Rankine cycle, and ejector refrigeration cycle (GT + ORC + ERC). This work has focused on environmental considerations and thermoeconomic evaluation to decrease destruction cost and environmental impacts. The examination of cycles is conducted from energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Cao et al [31] proposed a cogeneration system integrated with an ORC and a steam ejector, the thermal efficiency of which reached 79.0%. Fazali et al [32] observed that the exergy efficiency of an integrated system, including gas turbine, ORC, and ejector could reach 40.76%. Zhang et al [33] designed a novel cascade system based on a steam ejector and high-back-pressure technology, and the heating capacity increased by 4.21%.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [31] proposed a cogeneration system integrated with an ORC and a steam ejector, the thermal efficiency of which reached 79.0%. Fazali et al [32] observed that the exergy efficiency of an integrated system, including gas turbine, ORC, and ejector could reach 40.76%. Zhang et al [33] designed a novel cascade system based on a steam ejector and high-back-pressure technology, and the heating capacity increased by 4.21%.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Maruf et al 24 demonstrated the applicability of the exergetic sustainability method for the assessment of power generation scenarios at a national level using the situation in Bangladesh as a case study. The exergetic sustainability methodology has also been applied widely in assessing the environmental viability of waste treatment technologies as reported in a systematic literature review study by Soltanian et al 25 Regarding the exergoenvironmental method, Fazeli et al 26 employed an integrated exergy-based environmental assessment to demonstrate the effectiveness of waste heat recovery for multi-generation of energy products in an integrated system comprising a gas turbine, an ORC, and an ejector refrigeration cycle. Talebizadehsardari et al 27 carried out an exergoenvironmental analysis, among other exergy-based assessments, of an integrated energy system involving gas and steam turbines, ORC, and a carbon capture and storage (CCS) facility.…”
Section: Introductionmentioning
confidence: 99%